Pasos de Libertad: Transmedia proposal to strengthen the appropriation of heritage value - Fonseca, Andrea Carolina (Universidad de Boyacá, 2019)
This paper reflects on a proposal aiming to implement digital educational content through transmedial narratives that engage new generations in subjects such as the Ruta Libertadora (Route of Freedom) in Boyacá. The research problem deals with strengthening and disseminating the heritage and cultural value of this Route in unconventional environments for educational purposes. Following the analysis and diagnosis of a student community attending the Silvino Rodríguez School in Tunja, a prototype has been worked out and its development is described here. Focusing on the historical site Puente de Boyacá (Bridge of Boyacá), it is targeted at the students and includes script, content adaptation, voice dubbing, video recording, animation, character creation, a mobile application and an e-book. It is thus intended reducing the digital gap, fostering this type of content, making it more accessible and responding to the needs identified when working with the School’s young population.